Sustainability-informed maintenance optimization of highway bridges considering multi-attribute utility and risk attitude. (1st November 2015) - Sabatino, Samantha; Frangopol, Dan M.; Dong, You
Highlights: A single sustainability performance indicator is proposed for highway bridges. A robust sustainability-informed decision support framework is presented. Optimal maintenance plans are found considering multi-attribute utility theory. The risk attitude of the decision maker affects optimal intervention strategies. Abstract: Throughout their service life, highway bridges deteriorate due to increasing traffic loads and aggressive environmental conditions. Aging of materials can have significant effects on the structural performance of highway bridges. A comprehensive risk assessment procedure is crucial in evaluating and ultimately mitigating detrimental consequences of structural failure to the economy, society, and the environment. The proposed sustainability-based maintenance optimization decision-support framework provides decision makers with optimal life-cycle maintenance actions that balance conflicting objectives. Utility theory is employed herein in order to effectively capture the sustainability performance of highway bridges and impact of the decision maker's risk attitude. The main objective of this framework is to reduce the extent of the consequences of structural failure to the economy, society, and the surrounding environment. The capabilities of the proposed approach are demonstrated on an existing highway bridge.